Cripto: Expression, epigenetic regulation and potential diagnostic use in testicular germ cell tumors. Issue 4 (18th November 2015) - Spiller, Cassy M.; Gillis, Ad J.M.; Burnet, Guillaume; Stoop, Hans; Koopman, Peter; Bowles, Josephine; Looijenga, Leendert H.J.
Abstract : Type II germ cell tumors arise after puberty from a germ cell that was incorrectly programmed during fetal life. Failure of testicular germ cells to properly differentiate can lead to the formation of germ cell neoplasia in situ of the testis; this precursor cell invariably gives rise to germ cell cancer after puberty. The Nodal co‐receptor Cripto is expressed transiently during normal germ cell development and is ectopically expressed in non‐seminomas that arise from germ cell neoplasia in situ, suggesting that its aberrant expression may underlie germ cell dysregulation and hence germ cell cancer. Here we investigated methylation of the Cripto promoter in mouse germ cells and human germ cell cancer and correlated this with the level of CRIPTO protein expression. We found hypomethylation of the CRIPTO promoter in undifferentiated fetal germ cells, embryonal carcinoma and seminomas, but hypermethylation in differentiated fetal germ cells and the differentiated types of non‐seminomas. CRIPTO protein was strongly expressed in germ cell neoplasia in situ along with embryonal carcinoma, yolk sac tumor and seminomas. Further, cleaved CRIPTO was detected in media from seminoma and embryonal carcinoma cell lines, suggesting that cleaved CRIPTO may provide diagnostic indication of germ cell cancer. Accordingly, CRIPTO was detectable in serum from 6/15 patients with embryonal carcinoma, 5/15 patients with seminoma, 4/5 patients with germ cell neoplasia in situ cells only and in 1/15 control patients. These findings suggest that CRIPTO expression may be a useful serological marker for diagnostic and/or prognostic purposes during germ cell cancer management. Highlights: Promoter methylation of CRIPTO is differentially regulated between normal germ cell development and in germ cell tumors. CRIPTO is strongly expressed in the germ cell precursor cell GCNIS, EC, YST and SE. CRIPTO protein is cleaved from the cell surface and detectable in serum of patients with GCNIS‐only, EC, YST and SE.